2018
DOI: 10.2147/ott.s191041
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of syncytin-1 promotes invasion and metastasis by activating epithelial-mesenchymal transition-related pathway in endometrial carcinoma

Abstract: Background: Endometrial carcinoma (EC) is the most common and lethal malignancy worldwide. Syncytin-1 is expressed in multiple types of cancer. However, the expression pattern and potential mechanism of syncytin-1 and its clinical significance in EC remain unclear. Materials and methods: We analyzed 130 primary EC specimens from Binzhou Medical University to investigate the clinical role of syncytin-1 in EC by using different advanced pathological stages of EC tissues. Kaplan-Meier analysis was used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
0
29
0
1
Order By: Relevance
“…The PI3K/AKT signaling plays a pivotal role in the development of EC by regulating cell proliferation, invasion and EMT. 32 - 34 Hence, we further explored the role of KIFC1 in the regulation of PI3K/AKT signaling cascade. As displayed in Figure 5A , knockdown of KIFC1 reduced the protein expression of p-AKT and p-PI3 K, but had no significant effects on the protein expression of AKT and PI3K in Ishikawa cells.…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/AKT signaling plays a pivotal role in the development of EC by regulating cell proliferation, invasion and EMT. 32 - 34 Hence, we further explored the role of KIFC1 in the regulation of PI3K/AKT signaling cascade. As displayed in Figure 5A , knockdown of KIFC1 reduced the protein expression of p-AKT and p-PI3 K, but had no significant effects on the protein expression of AKT and PI3K in Ishikawa cells.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we looked at possible abnormal HERV activation in blood samples from women with recurrent miscarriages, but we did not find any alterations (unpublished data). In contrast, enhanced HERV expression is associated with development and invasion of several cancers, e.g., the up-regulation of syncytin-1 promotes the malignant transformation of hydatidiform moles (32) and the spread of endometrial carcinoma (33), and all malignancies of placental origin (including those of late appearance) derive from cells of the conceptus, not of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been no large population-based case-control study on the correlation between EC and other tumors, Schildkraut et al [33] found a signi cant association between breast cancer and ovarian epithelial tumor with EC in familial cases. In addition, Liu et al [34] found that overexpression of syncytin-1 promoted the invasion and metastasis of EC cells by activating epithelial-to-mesenchymal transitionrelated pathways. Consistently, in this study, the WGCNA con rmed that a history of other malignancies was positively correlated with the MEbrown module.…”
Section: Discussionmentioning
confidence: 99%